Age-related hearing loss in older adults with cognitive impairment. (22nd September 2016) - Nirmalasari, Olivia; Mamo, Sara K.; Nieman, Carrie L.; Simpson, Allison; Zimmerman, Jessica; Nowrangi, Milap A.; Lin, Frank R.; Oh, Esther S.
ABSTRACT: Background: Hearing loss can impair effective communication between caregivers and individuals with cognitive impairment. However, hearing loss is not often measured or addressed in care plans for these individuals. The aim of this study is to measure the prevalence of hearing loss and the utilization of hearing aids in a sample of individuals with cognitive impairment in a tertiary care memory clinic. Methods: A retrospective review of 133 charts of individuals >50 years who underwent hearing assessment at a tertiary care memory clinic over a 12-month period (June 2014–June 2015) was undertaken. Using descriptive statistics, the prevalence of hearing loss was determined and associations with demographic variables, relevant medical history, cognitive status, and hearing aid utilization were investigated. Results: Results indicate that hearing loss is highly prevalent among this sample of cognitively impaired older adults. Sixty percent of the sample had at least a mild hearing loss in the better hearing ear. Among variables examined, age, MMSE, and medical history of diabetes were strongly associated with hearing impairment. Hearing aid utilization increased in concordance with severity of hearing loss, from 9% to 54% of individuals with a mild or moderate/severe hearing loss, respectively. Conclusions: Hearing loss is highly prevalent among older adults with cognitive impairment. Despite high prevalence of hearing loss, hearing aid utilization remains low. Our study highlights the importance of hearing evaluation and rehabilitation as part of the cognitive assessment and care management plan in this vulnerable population.